Osmotic management of distributed complex systems: A declarative decentralised approach. Issue 10 (7th November 2021) - Forti, Stefano; Lera, Isaac; Guerrero, Carlos; Brogi, Antonio
Abstract: Osmotic computing encompasses emerging Cloud‐Internet of Things (IoT) computing paradigms, by featuring the possibility for application services to adapt into different functionally equivalent flavours, depending on the contextually available resources and on specific requirements of running applications. This article proposes a fully decentralised declarative framework that enables both application and infrastructure operators to declare management policies for the service instances and the nodes they manage, respectively. Policies are composed of a simple and well‐defined set of management operations, declared in Prolog, which trigger based on locally available contextual information on application requests and infrastructure resources. A prototype implementation of the framework is showcased and assessed via simulation over a lifelike Smart Campus use case with multiple applications, at increasing infrastructure sizes and number of mobile users. Experimental results show that the proposed management framework scales to large infrastructure sizes and suits the needs of multiflavoured Osmotic applications in dynamic deployment conditions, by improving the trade‐off between their response times and suitable service usage. Abstract : We propose a fully decentralised declarative framework that enables both application and infrastructure operators to declare management policies for the service deployment in Cloud IoT infrastructures.